Chemical Profiling of Black Tea Polyphenols - Imran, Ali; Butt, Masood Sadiq; Sharif, Mian Kamran; Sultan, Javed Iqbal (Pakistan Journal of Nutrition, 2013)
In present project locally grown black tea (Qi-men variety) was explored for its nutritional and antioxidant potential. Furthermore, polyphenols extraction was carried out by using water, ethanol and methanol as solvent at varying time conditions. Proximate profiling indicating moisture, crude fat, crude protein, crude fiber, ash and NFE as 7.01±0.20, 4.51±0.06, 15.12±0.51, 15.33±1.52, 4.86±0.08 and 53.17±1.97%, respectively. Likewise, tested sample exhibited good mineral status dominated by potassium and sodium. The different antioxidant indices were affected significantly by time and solvents. In this context, ethanol and 60 min extraction time showed maximum TPC, FRAP, DPPH and beta-carotene activity as 1150.92±15.01 and 833.33±1.12 mg/100g GAE, 754.44±12.30 and 609.89±16.04 μmolFe2+/g, 71.13±3.20 and 65.32±3.26 and 67.74±3.10 and 66.24±3.90%, respectively whilst minimum amount of these attributes were recorded in water extract and 30 min extraction time by 354.02±5.12 and 656.44±11.05 mg/100gGAE, 471.78±12.50 and 558.00±14.03 μmol Fe2+/g, 55.27±3.14 and 59.69±2.30 and 48.27±3.90 and 61.30±2.90%, correspondingly. Likewise, theaflavin, thearubigins, catechins and caffeine contents were detected highest in ethanolic extract 2.55±0.25, 20.93±1.10, 1.90±0.02 and 1.89±0.01% followed by methanol 2.05±0.25, 19.45±1.8, 1.68±0.03 and 1.72±0.06% and water extracts 1.23±0.25, 17.69±1.30, 1.52±0.04 and 1.54±0.03%, respectively. Among the time intervals, 60 min proved more efficient for the extraction of these bioactive moieties than that of 90 and 30 min. Conclusively, the tested black tea extracts holds promising antioxidant status thus prove as potential candidates against lifestyle related disorders.